Optimization of Organic Waste Processing Using Bio-Compound Method Through Pineapple Fermentation - I Made Arie Widyasthana Wartana Putra; Almer Rasyid; Aghniya Salsabila Wardhani; Putri Kusuma Ningrum (CV. Creative Tugu Pena, 2024)
Waste processing through pineapple fermentation is one of the efforts to improve environmental cleanliness and also as a form of optimizing the lack of understanding of environmentally friendly and sustainable waste management practices. This community service activity aims to increase community awareness and understanding of the urgency of processing organic waste as a solution to increasingly critical environmental problems and equip participants with practical skills in processing organic waste into products that have added value, both from an economic and ecological perspective and encourage active community involvement in waste management at the household level as the smallest unit in the community structure, which is later expected to create long-term effects in waste management at a broader level. With a participatory approach, involving community activities in all stages, this community service build understanding and enthusiasm among residents. The results show that the community empowerment carried out in RW 07 Karang Besuki Village is that the community understands how to process waste easily does not require a long time in the process, and produces useful products that are also economically and socially empowering. Hopefully, through the socialization and training provided, the community will continue to care about their environment, especially environmental cleanliness.